Influence of innovation on small and medium enterprise (SME) growth: The case of wood and steel furniture manufacturing in Dodoma City - John, Stephen (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University as a partial fulfillment of the requirements for award of degree of Masters of Science in Entrepreneurship Development (MSC. ED) of Mzumbe University